PENGARUH RASIO LIKUIDITAS, SOLVABILITAS, AKTIVITAS, PROFITABILITAS DAN RASIO PASAR TERHADAP PERUBAHAN LABA (Studi Kasus Perusahaan Sektor Telekomunikasi Terdaftar di Bursa Efek Indonesia) - Susanna Hutabarat (Universitas Mercu Buana, 2013)
Abstract: One of information about financial performance is the earning. The earningcan show the positive signal about the prospect of a company in the future. Theearning can increase or decrease for every year or every period. The aim of thisresearch is to analyze the influence of financial ratio to earning changes in companiesof telecommunication sector in Bursa Efek Indonesia. Population in this research werecompanies which listed on the BEI in the period 2010-2011, totally 6 companies andsamples are 4 companies. There are 5 independent variables, those are Current Ratio(CR) as liquidity ratio, Debt Ratio (DR) as solvability ratio, Total Asset Turn Over(TATO) as activity ratio, Return on Equity (ROE) as profitability ratio and PriceEarning Ratio (PER) as market ratio.The results of this research indicate that CR, DR,TATO, ROE and PER influence simultaneously to earning changes. Based on model-2, partially CR has a positive significant influence, TATO has a negative significantinfluence, ROE has a positive significant influence, and PER has a negative significantinfluence. DR has no the significant influence to earning changes. The most significantinfluence comes from ROE (profitability ratio).Keywords: Earning Changes, Current Ratio, Total Asset Turn Over, Return onEquity, Price Earning Ratio